Business Simulation Game Design Based on Real Time Strategy Using SpringRTS Engine - Muhammad Alfian Jauhari; Muhammad Akid Musyafa; Muhammad Dzulfikar Fauzi; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2015)
Competition in today's business world is getting tougher and raises the number of changes, in which the changes occur more rapidly. Because of that the ability and skills of human resources should also be able to learn quickly to adapt the changes in business world. Therefore, entrepreneur needs a tool that can give the effect of teaching and improve the ability of decision-making and reduce the financial risk for businesses. This research aims to develop a game which can do business simulation. In the process of developing this game, SpringRTS framework is used to maintain the development. There are some steps being taken, which originated from the literature study followed by analysis and design requirements and proceed with expressing ideas that have been done on the analysis and design steps into a tangible form, which includes 3d modeling, uv texture mapping, 3d assembling and coding with the Lua programming language. This research successfully produces business simulation game that can give the effect of teaching in a game without compromising the beauty of the graphics aspect according to research output which made a simulation game with 3 dimensional graphics which make the user whom played it did not easy to became bored.